Zarząd majątkami małżonków: [Management of common property of the spouses] (Studia Prawnicze / The Legal Studies, 1981)
The purpose of this paper is to analyse the issue of management of common property of the spouses from the point of view of its conformity with the principles of Polish family law.Common property constitutes community of joint-type and is regulated in the family and guardianship code. However, in case of absence of respective detailed norms, provisions of the civil code on coownership in fractional shares are correspondingly applied by way of analogy.All legal acts undertaken in connection with common property may be devided into two groups: acts of ordinary management and acts going beyond the scope of ordinary management. To the latter group also acts having the character of dispositions were included. De lege lata we should interpret "acts of ordinary management" of common property in a wide way and connect such interpretation with the circumstances of a given case. Entering legal transactions of ordinary management, a spouse acts exclusively in his own name and not as a representative of the other spouse. When acts going beyond ordinary, management are concerned, a spouse giving his consent to such an act undertaken by the other, does not become a party to the transaction but remains a third party in relation to it. The Author of this article is of the opinion that provisions regulating common property of the spouses cannot be invoked a legal foundation to qualify a spouse as a person performing an act of management concerning common property as a party to such transaction, or - at least - as a party to legal relationship so created.In practice, from among various means ensuring the right of a spouse to manage common property, only proceedings aiming at deprivation of a spouse of this right and court rulings concerning significant family matters in case of disagreement of the spouses play more significant role. Suitability of instituting proceedings based on article 40 of the family and guardianship code is present in case common property is endangered in result of undertaking certain acts not agreed upon with another by one of the spouses only. Such proceedings are to prevent future acts connected with common property and do not turn on liquidation of misunderstandings existing between the spouses in reference to a given transaction. The latter situation is regulated by art. 24 of the family and guardianship code. On the basis of this article the court may rule only in connection with matters, which may be regulated by way of mutual agreement by the spouses themselves. As for the acts of ordinary management, agreement in the inner relation between the spouses should exist. In its absence (in case of significant family matters), proceedings based on article 24 of the family and guardianship code are applicable. The principle of undertaking acts legal with the consent of the spouses (art. 24) concerns also management of those elements of separate property? which are most important for the family.Present regulation of the principles of management of common property should be changed by limiting the requirement of entering legal transactions by both spouses only to management concerning these elements of common property which are most important for the whole family.Some exceptions . from the principles of management of common property are contained in the law on cooperatives and in law on retirement pensions for the farmers, and they should be estimated in a negative way. On the other hand, provisions contained in the law on banks, differing from provisions of the family and guardianship code in that respect, do not raise such reservations.